Faktor-Faktor yang Mempengaruhi Motivasi Belajar Matematika Siswa: Sebuah Kajian Literatur - Rohmatul Hasanah; Ucik Fitri Handayani (Program Studi Tadris Matematika Fakultas Tarbiyah Institut Agama Islam Al-Qolam Malang, 2025)
The issue of low mathematics learning outcomes remains unresolved to date. Various efforts have been made, including implementing diverse learning models. To develop these models, it is crucial to understand students' learning styles and motivating factors. In this article, researchers examine aspects influencing students' motivation in mathematics learning, including peer influence. The study aims to identify and analyze variables influencing students' desire to learn mathematics, thereby formulating effective strategies to enhance their motivation. Data was collected by compiling and analyzing literature related to factors influencing student motivation in mathematics learning. The analysis involved five articles indexed in Sinta, utilizing content analysis as the research technique. Findings indicate two primary factors influencing student motivation: internal factors such as physical condition, intelligence, learning patterns, emotional state, health, motivation to succeed, drive to fulfill learning needs, and aspirations; and external factors including learning environment, educational facilities, study schedules, interactions with teachers and parents, recognition, and engaging learning activities. Researchers recommend that teachers employ various teaching approaches to maintain student engagement and prevent boredom. When students study at home, parents are encouraged to continue providing encouragement and guidance.